2017
DOI: 10.4238/gmr16018710
|View full text |Cite
|
Sign up to set email alerts
|

Identification of lipopeptides produced by Bacillus subtilis Czk1 isolated from the aerial roots of rubber trees

Abstract: ABSTRACT. We obtained a strain of Bacillus subtilis, which we named Czk1, from the aerial roots of rubber trees. This bacterial isolate exhibits strong antagonistic activity against Ganoderma pseudoferreum, Phellinus noxius, Helicobasidium compactum, Rigidoporus lignosus, Sphaerostilbe repens, and Colletotrichum gloeosporioides. Our earlier research has shown that the antagonistic activity of a fermentation supernatant Czk1 isolate produces a complex mixture of lipopeptides. In this study, we used methanol to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 40 publications
0
8
0
1
Order By: Relevance
“…Trichoderma spp., Bacillus spp., and Streptomyces spp. were shown to have antagonistic activity against P. noxius and could effectively reduce BRR in greenhouse assays (Schwarze et al ., 2012; Ribera et al ., 2016; He et al ., 2017; Shafi et al ., 2017; Chou et al ., 2019; Leung et al ., 2020). Burkholderia cenocepacia 869T2, an endophytic bacterium used to control Fusarium wilt in banana, was observed to temporarily inhibit the growth of P. noxius in dual‐cultures.…”
Section: Introductionmentioning
confidence: 99%
“…Trichoderma spp., Bacillus spp., and Streptomyces spp. were shown to have antagonistic activity against P. noxius and could effectively reduce BRR in greenhouse assays (Schwarze et al ., 2012; Ribera et al ., 2016; He et al ., 2017; Shafi et al ., 2017; Chou et al ., 2019; Leung et al ., 2020). Burkholderia cenocepacia 869T2, an endophytic bacterium used to control Fusarium wilt in banana, was observed to temporarily inhibit the growth of P. noxius in dual‐cultures.…”
Section: Introductionmentioning
confidence: 99%
“…Results above showed that the compound obtained in this research was different from general compound produced by Bacillus subtilis such as surfactine that has weight of 994 -1.065 m/z 3,4,6 iturine which is weighed 1.028 -1.109 m/z 4,5 , bacillomycine that has weight 1081 m/z 6 , fengisine weighed 1.421 -1.566 m/z 3,4,5,6 , and subtilisine which has weight 3.399 -3.473 m/z 4 .…”
Section: Resultsmentioning
confidence: 72%
“…Bacillus subtilis was reported to have ability to inhibit soil phytopathogen because it has the ability to produce antibiotics, such as lipopeptide antibiotics 1,2 . Antibiotic compounds produced by Bacillus subtilis are surfactine 3,4 , iturine 4,5 , bacillomycine 6 , fengicine 5,6 , and subtilicine 4 . In our previous research, Bacillus subtilis AAF2 was reported to have the ability to inhibit the growth of phytopathogen.…”
Section: Introductionmentioning
confidence: 99%
“…The results of these authors showed that PCR products of sfp, srfD, fenB, ituA, and ituC were amplified. He et al [33] reported the presence of the LP genes sfp (surfactin), fenB (fengycin), ituD (iturin) in B. subtilis Czk1, which was obtained from the aerial roots of rubber trees. It was contemplated that the co-production of several LPs by one strain can increase their synergistic effect [34].…”
Section: Discussionmentioning
confidence: 99%